1961
DOI: 10.1001/archinte.1961.03620050005002
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Hypercholesteremia by Nicotinic Acid

Abstract: to summarize our experience for the period 1956 to 1960, present our current recom¬ mendations in light of this additional ex¬ perience, and review numerous studies related to the mechanism of action of nicotinic acid, which still remains unknown.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0

Year Published

1962
1962
1992
1992

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(8 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…However, the gradual disappearance of visible cholesterol deposits in the skin and tendons leads to the hope that similar changes may occur in early atherosclerotic plaques and other portions of the arterial wall which readily exchange cholesterol with the serum. Reduction in xanthoma tuberosum in 2 of our patients has been reported elsewhere (4).…”
Section: Response Of Serum Cholesterol Levelsupporting
confidence: 81%
“…However, the gradual disappearance of visible cholesterol deposits in the skin and tendons leads to the hope that similar changes may occur in early atherosclerotic plaques and other portions of the arterial wall which readily exchange cholesterol with the serum. Reduction in xanthoma tuberosum in 2 of our patients has been reported elsewhere (4).…”
Section: Response Of Serum Cholesterol Levelsupporting
confidence: 81%
“…Furthermore, it has been shown that the plasma total lipids and total esterified fatty acids also decrease during nicotinic acid treatment (3,4). Cutaneous xanthomata such as xanthoma tuberosum have been reported to disappear in several cases (2). These findings indicate that nicotinic acid has a major action not only on plasma cholesterol but also on elevated plasma glyceride levels.…”
mentioning
confidence: 87%
“…While the prolonged administration of niacin has been reported to cause growth inhibition and fatty liver in rats (24), this compound, like the other water-soluble vitamins, is generally considered to be nontoxic since it is readily metabolized and excreted. Niacin at doses many times greater than the conventionally accepted vitamin levels has been used clinically as a vasodilatory agent as well as a hypolipidaemic-hypocholesterolaemic drug (25,26). The aim of the present investigation was to determine whether niacin offers protection against BLM-induced lung fibrosis in hamsters.…”
Section: Introductionmentioning
confidence: 99%